UJI EFEKTIVITAS EKSTRAK DAUN SRIKAYA (Annona squamosa) DALAM MENGHAMBAT PERTUMBUHAN Trichophyton rubrum SECARA IN VITRO DENGAN METODE DIFUSI SUMURAN - Hanif Siraj (2021)
Dermatofitosis is a superficial mycosis caused by dermatophytes that produce keratinase enzymes to digest keratin in hair, nails, and stratum corneum on the skin. Trichophyton rubrum is a common causative agent of dermatophytosis. Sugar apple (Annona squamosa) is a plant whose leaves have substances such as flavonoids, saponins, tannins, and terpenoids that have antimicrobial and antifungal properties. The aim of this study is to determine the effectiveness of administration of sugar apple leaf extract (Annona squamosa) in inhibiting the growth of Trychophyton rubrum in vitro. This research is purely experimental with post-test only control group design. The methods used are maceration method using 70% ethanol solvent and well diffusion method. The concentration of sugar apple leaf extract used is 5%, 10%, 20%, and 50% accompanied by positive control (ketoconazole) and negative control (ethanol 70%). Data is analysed using One Way Anova test. The results exhibit the average diameter of inhibitory zones sequential from the smallest concentration are 3.06 mm, 3.45 mm, 6.31 mm, and 13.98 mm. The One Way Anova test showed a value of p = 0.00 (p < 0.05) indicating that there is a remarkable difference in the inhibitory zone of sugar apple leaf extract (Annona squamosa) between concentration groups towards the growth of Trychophyton rubrum. Concentration of 50% is the best concentration to inhibit the growth of Trychophyton rubrum with the average value of the diameter of the inhibitory zone at that concentration is categorized as potentially strong antifungals. The conclusion of this study is that the sugar apple leaf (Annona squamosa) extract is effective in inhibiting the growth of Trychophyton rubrum.